Double Taxation Treaties and Their Implications for Investment: What Investment Policymakers Need to Know - UN Trade; Development (United Nations, 2024)
This guide complements the “twin” guide on international investment agreements (IIAs) and their implications for tax measures published in 2021 by UNCTAD in cooperation with the WU Global Tax Policy Center. It equally aims to stimulate interaction between investment policymakers and DTT negotiators. This guide aims to bridge the gap between investment and tax policy, complementing a previous guide on IIAs. Its detailed exploration of DTTs, providing insights into their structure, functioning, and impact on international investment, advocates for a synergistic approach between tax and investment policymaking. The guide emphasizes the importance of coherent policies to support sustainable development and economic growth.